Global existence of solutions to parabolic Monge–Ampère equations on Riemannian manifolds. (April 2015) - Ru, Qiang
Abstract: In this paper, we study the Cauchy problem of the parabolic Monge–Ampère equation u t − log g − 1 det ( g i j + ∇ i j u ) = − n log u in M n × ( 0, ∞ ), u ( x, 0 ) = u 0 ( x ) in M n, where M n is a compact complete Riemannian manifold of dimension n ≥ 2, g i j denotes the metric of M n